ROLE OF NON-PERFORMING ASSETS- A MSMES PERSPECTIVE IN INDIA - Deveshwar, Aarti; Yadav, Diksha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Micro, Small, and Medium Enterprises (MSMEs) sector is a major contributor to the socio-economic development of India, significantly impacting GDP and exports. Particularly in semi-urban and rural areas, MSMEs foster entrepreneurship, generate employment, and play a pivotal role in poverty reduction. This sector is the second largest employer in India after agriculture, characterized by its dynamism and vibrancy. Banks play an indispensable role in mobilizing resources and supporting diverse economic sectors. The growth and development of MSMEs are heavily reliant on timely and adequate access to financial services. NPA is also the biggest challenge in the development of the Banking system. Majority of the studies analysis the Non-Performing Assets of banking sector. But very less studies are conducted in NPA with reference to specific sector i.e. MSMEs, so NPA related to MSME also be assessed in the study. The study analysis of Non-Performing Assets (NPAs) in the context of scheduled commercial banks (SCBs) in India, with a specific focus on their credit exposure to the Micro, Small and Medium Enterprises (MSME) sector. This objective brings forth crucial insights into the financial health and risk management efficacy of these banks in relation to their MSME lending.